(untitled) (Tanzania Medical Journal, 2020)
Background Chest X-ray radiography is a widely available and cheap imaging modality used for identification of pulmonary tuberculosis (PTB) in suspected patients. Knowledge of discriminatory features of PTB among HIV infected patient is of utmost importance to improve tuberculosis case detection and consequently reduce morbidity and mortality associated with TB among HIV infected individuals. We aimed to describe chest radiographic findings among PTB patients and their association with HIV co-infection and CD4 levels among HIV positive patients. Methodology A total of 170 newly diagnosed consented smear positive PTB patients underwent postero-anterior Chest radiographs (PA - CXR) and HIV testing. Determination of CD4 count was performed among HIV positive patients. The radiographs were interpreted using glossary of terms for thoracic radiology by two independent radiologists who were blinded to HIV diagnosis. Results Study participants included 100 (58.9%) males and 70 (41.1%) females. Among these 54 (31.8%) had HIV/PTB co-infection. The pattern of radiographic findings among patients with PTB/HIV compared to PTB only were: pulmonary cavities 44.4% vs 61.2%, (p=0.04), alveolar consolidation 64.9% vs 81.7%, (p=0.04), upper zone consolidation 40.7% vs 57.8%, (p=0.039), middle zone consolidation 25.9% vs 44.8%, (p=0.019) and typical PTB 40.7% vs 57.8%, (p=0.039), respectively. Therefore, lesions were less likely to be observed among PTB/HIV compared to PTB only and the differences were statistically significant. When compared to PTB patients only HIV/PTB co-infected patients had more nodules on the left lung field 85.2% vs 60.9% (p=0.023); on each left lung zone upper 59.3% vs 34.4% (p=0.028); mid 77.8% vs 54.7% (p-value=0.039); lower 66.7% vs 34.4% (p=0.005) and miliary nodules 44.4% vs 15.6% (p=0.003), respectively. HIV/PTB co-infected patients with CD4 > 200 cells/?L had more mid zone consolidation (42.9% vs 15.2%, p=0.024). Conclusion The commonest chest radiographic findings in HIV/PTB co-infected patients were pulmonary cavities and alveolar consolidation are associated with HIV negative status. HIV/PTB co-infected patients with severe immunosuppression had mid zone consolidation. Patients with severe immunosuppression showed less chest radiographic findings. HIV/PTB co-infection was highly associated with mid and lower zone pulmonary nodules and miliary nodules. Key words: PTB, HIV, CXR